Utilization of Cassava Processing Liquid Waste as Raw Material for Making Biodegradable Plastics with the Addition of Glycerol Plasticizer - Iswendi Iswendi; Iryani Iryani; Alpira Alpira; Regi Fadila Putra (EKSAKTA: Journal of Sciences and Data Analysis, 2021)
This study aimed to utilize cassava processing liquid waste into biodegradable plastic with glycerol as a plasticizer. This experimental study varies the amount of glycerol: (0, 1, 2, 3, 4, and 5) mL. The resulting biodegradable plastics were analyzed for physical properties consist of (water content and degree of swelling), mechanical properties consist of (tensile strength, elongation, elasticity), biodegradation, and structural properties. Fourier Transform Infra-Red and x-ray diffraction were employed for the studies. The results showed that the more glycerol added, the greater the percentage of water content and the degree of swelling were obtained. The optimum tensile of the biodegradable plastic was reached with 3 mL of glycerol, giving the strength of 27.49 N/mm2, elongation 0.107 N/mm2, elasticity 4.804 MPa. Biodegradable plastic with the addition of 5 mL of glycerol degraded up to 60.777%. The FTIR spectra showed almost the same peaks between plastics without the addition of glycerol and glycerol. Meanwhile, XRD data shows that the degree of crystallinity of plastic without glycerol is higher than that of plastic with the addition of glycerol.